Differentiation of Strains of Yellow Fever Virus in γ-irradiated mice - Fitzgeorge, R.; Bradish, C. J. (Journal of General Virology, 1980)
SUMMARY The mouse sensitized by optimal, sub-lethal γ-irradiation has been used for the differentiation of strains of yellow fever virus and for the resolution of their immunogenicity and pathogenicity as distinct characteristics. For different strains of yellow fever virus, the patterns of antibody-synthesis, regulatory immunity (pre-challenge) and protective immunity (post-challenge) are differentially sensitive to γ-irradiation. These critical differentiations of strains of yellow fever virus in γ-irradiated mice have been compared with those shown in normal athymic and immature mice in order to elucidate the range of quantifiable in vivo characteristics and the course of the virus-host interaction. This is discussed as a basis for the comparison of the responses of model and principal hosts to vaccines and pathogens.